Saberes ancestrais femininos na filosofia africana: poéticas de encantamento para metodologias e currículos afrorreferenciados - Machado, Adilbênia Freire (2019)
Given the lack of epistemological, methodological and curricular appreciation in an Afro-referenced perspective for research on Africanities, besides the sexism that makes women unfeasible in the construction of contemporary African philosophy, even in cultures marked by matriarchy, this thesis aims to contribute to the decolonization of knowledge, curricular and methodological decolonization from African, Afro-Brazilian philosophies of ancestry and enchantment crocheted by female ancestral knowledge and its relation to education. As black people it is imperative that we build our epistemologies and ways of teaching / learning based on our own categories and trajectories. Thus, we question the naturalization and universalization of the phallocentric privilege, cisgender and white, as an order of thought and existence itself. We present Afro-referenced theoretical-methodological proposals, especially the Odus Methodology, which outlined the construction of this thesis, as well as curricular proposals, as well as a female theoretical framework in a perspective of transversality, inclusion and valorization of knowledge denied by the West. Therefore, we seek to bring reflections from our own experiences, about decolonization of the senses (being / doing / learning / teaching / knowing / feeling), the cosmossensations, in order to build epistemologies for an engaged and libertarian education. Privileging the poetics of enchantment, the experiences woven into our words, our writings, our knowledge crocheted by the scribes of our feminine bodies full of senses, (re) existences and the ancestry that enables and enhances the very existence of / in the world. We propose, therefore, Afro-referenced, anti-racist, antisexist dialogues and connected with the poems of enchantment, that is, with the cosmoencantamento, the black feminine ancestral knowledge, problematizing the proper intersectionality of existences marked by diverse oppressions arising from racism, gender inequalities, of sexuality and social class, but also to speak from the power of life and from the very possibility of existing, of creating, of being. African philosophies come from the feminine, because ancestry is feminine, so these philosophies are implicated in the return to the feminine as the main source of and for life.